2016
DOI: 10.21577/0100-4042.20160184
|View full text |Cite
|
Sign up to set email alerts
|

Celdas solares sensibilizadas con colorantes fotosensibles obtenidos de plantas de la región sur de Ecuador

Abstract: SENSITIZED SOLAR CELLS WITH PHOTOSENSITIVE DYES OBTAINED FROM PLANTS OF THE SOUTHERN REGION OF ECUADOR.Four vegetal species of the southern of Ecuador were used as sensitizers for making dye-sensitized solar cells (DSSCs). The effect of type and amount of material, type and time of maceration were tested in order to determine the best conditions of extraction. The extraction of the natural dye was made with acidified ethanol. The sensitizing agents were adsorbed on TiO 2 nanoparticles in small solar cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This indicates that the anthocyanins extracted from each vegetable dye dissolve better in polar aprotic solvent such as ethyl acetate, demonstrating the importance of selecting a suitable solvent for anthocyanin purification. Similar findings have been reported by other researchers, they revealed that polar aprotic solvent such as dimethyl formamide, dimethyl sulfoxide, and acetone managed to extract more anthocyanins from Ixora coccinea flower than those of polar protic solvents such as ethanol and distilled water (Lim et al 2015;Wongcharee et al 2007;Cabrera et al 2017).…”
Section: Purification and Absorption Spectra Of Extracts From Jamaicasupporting
confidence: 90%
See 3 more Smart Citations
“…This indicates that the anthocyanins extracted from each vegetable dye dissolve better in polar aprotic solvent such as ethyl acetate, demonstrating the importance of selecting a suitable solvent for anthocyanin purification. Similar findings have been reported by other researchers, they revealed that polar aprotic solvent such as dimethyl formamide, dimethyl sulfoxide, and acetone managed to extract more anthocyanins from Ixora coccinea flower than those of polar protic solvents such as ethanol and distilled water (Lim et al 2015;Wongcharee et al 2007;Cabrera et al 2017).…”
Section: Purification and Absorption Spectra Of Extracts From Jamaicasupporting
confidence: 90%
“…In general, predominance of hydroxyl groups on the aromatic skeleton of anthocyanin gives rise to an intense blue color, while a red color is observed when methoxyl groups prevail instead (Vekariya et al 2016;Nayaran 2012). Anthocyanin compounds have also reported to be found in mora (berries), berenjena (eggplant), rabano (radish), tomate de arbol (tamarillo), ataco (amaranthaceae) and achiote (Wongcharee et al 2007;Polo and Iha 2006;Cabrera et al 2017;Tekerek et al 2011;Chang and Lo 2010). Corresponding natural dyes extracted in ethanol were evaluated as photosensitizers of DSSC, for example, Jaboticaba skin (Myrciaria cauliflora) reported a maximum absorption peak at 538 nm, attributed to peonidin as the principal anthocyanin compound (Polo and Iha 2006); it was also found that the absorption peak of rosella flowers (Hibiscus sabdariffa) extract was about 520 nm, and the anthocyanins obtained from rosella were delphinidin and cyaniding (Calogero et al 2012(Calogero et al , 2015Borras-Linares et al 2015), whereas an absorption peak of blue pea extracts was about 580-620 nm, responsible for its blue color, and the anthocyanin obtained was ternatin (Wongcharee et al 2007).…”
Section: Absorption Spectra Of Vegetable Dyes Photosensitizersmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the anthocyanin structure can also affect the performance of the devices. It is predicted that a structure with longer R group will result in the hinderance for the anthocyanin to form bond with the oxide in TiO 2 [27,28]. Similarly, difference in dye structure and rate of charge injection into TiO 2 conduction band is responsible for the difference in the current densities [29].…”
Section: Resultsmentioning
confidence: 99%